PERAN STRATEGI BISNIS INOVATIF DAN KINERJA KOPERASI GUNA MENINGKATKAN KESEJAHTERAAN ANGGOTA : Studi Pada Anggota Koperasi Wanita di Kota Malang - Wiastono, Agus (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2024)
This study aims to examine the impact of innovative business strategies and cooperative performance on the well-being of members. The research uses a quantitative approach, with a sample of 120 female cooperative members in Malang City. The data used in this study is primary data obtained through questionnaires. The analysis tools employed are multiple linear regression, F-test, and T-test. The results show that innovative business strategies implemented by cooperatives, particularly through visionary and responsive leadership, significantly influence the improvement of members' well-being, including increased income, Net-Profit Distribution, and financial access, as well as improvements in health and nutrition. Therefore, it is recommended that women's cooperatives in Malang strengthen innovative leadership, manage finances transparently, innovate in financial services, and introduce health programs to enhance member well-being and support the sustainability of the cooperative.